2020
DOI: 10.1002/hep4.1489
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Diversity in Expression of Organic Anion Uptake Transporters in Normal and Cirrhotic Human Liver

Abstract: Abbreviations: GFP, green fluorescent protein; MS, mass spectrometry; NTCP, Na + -taurocholate transporting polypeptide; OATP, organic anion transport protein; PBS, phosphate-buffered saline; PVDF, polyvinylidene difluoride; SDS-PAGE, sodium dodecyl sulfate-polyacrylamide gel electrophoresis; sfGFP, superfolder green fluorescent protein; SLC, solute carrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
(56 reference statements)
1
12
0
Order By: Relevance
“…This study and other recent reports suggest variability in the impact of cirrhosis on the expression of transporters according to the disease severity and the underlying pathophysiology (viral, alcoholic, and biliary diseases). ,, Drozdzik et al showed a progressive decline in the expression of NTCP, OATP1B1/2B1, OCT1, and MRP2 in line with our findings, but we also showed a progressive decline in the expression of BSEP, MRP3, OAT2, OCT3, and OATP1B3 in cirrhosis, which they did not. It is worth noting that associated diseases to cirrhosis in the two sets of samples are different (ours includes NAFLD, cancer, and cholestasis, while Drozdzik et al.…”
Section: Discussionsupporting
confidence: 92%
“…This study and other recent reports suggest variability in the impact of cirrhosis on the expression of transporters according to the disease severity and the underlying pathophysiology (viral, alcoholic, and biliary diseases). ,, Drozdzik et al showed a progressive decline in the expression of NTCP, OATP1B1/2B1, OCT1, and MRP2 in line with our findings, but we also showed a progressive decline in the expression of BSEP, MRP3, OAT2, OCT3, and OATP1B3 in cirrhosis, which they did not. It is worth noting that associated diseases to cirrhosis in the two sets of samples are different (ours includes NAFLD, cancer, and cholestasis, while Drozdzik et al.…”
Section: Discussionsupporting
confidence: 92%
“…These transporters form a superfamily of membrane-solute carriers characterized by significant functional diversity and a widespread role in the transport of endo/xenobiotics ( Hagenbuch and Meier, 2004 ). There is scarce data on whether they are involved in the brain transport of psychotropics, but we know that transport of DHEA-S and opioids occurs via OATP1A2 and a small sex difference favoring women was recently reported ( Asaba et al, 2000 ; Gao et al, 2000 ; Taniguchi et al, 2020 ). However, DHEA administration led to a gender-neutral Oatp1a1 and Oatp1b2 decrease and a further decrease in Oatp1a4 expression only in males ( Rost et al, 2005 ).…”
Section: Organic Anion Transporting Polypeptidesmentioning
confidence: 99%
“…There are already pieces of evidence that female rats have greater BBB permeability of taurocholate and atorvastatin, which are carried by Oatp1a4/Slco1a4 (an ortholog for human OATP1A2), compared to the corresponding brain uptake of these compounds with male rats (151). A similar kind of trend has been seen in RNA expression of OATP1A2 collected from the human liver samples; females had approximately twice greater OATP1A2 mRNA expression compared to that in men (P < 0.05) (152). Therefore, more studies are warranted to elucidate the age-, race-, and gender-related effects on the pharmacoproteomics, not only OATP1A2 substrates but also other transporters at the CNS-barriers (Fig.…”
Section: Prospectsmentioning
confidence: 60%